Respuesta :
-7(x-3)-27=-6
To evaluate, we will use PEMDAS, so then parenthesis will come first:
-7x+21-27=-6
We have no exponents, multiplication, or division, so addition/subtraction of like terms will be our next step.
-7x-6=-6
Now we can solve for x. To do this, we will first isolate the -7x by adding 6 to both sides.
-7x=0
We will then isolate x by dividing both sides by -7, which will give us:
x=0
To evaluate, we will use PEMDAS, so then parenthesis will come first:
-7x+21-27=-6
We have no exponents, multiplication, or division, so addition/subtraction of like terms will be our next step.
-7x-6=-6
Now we can solve for x. To do this, we will first isolate the -7x by adding 6 to both sides.
-7x=0
We will then isolate x by dividing both sides by -7, which will give us:
x=0
Answer:
x = 0
Step-by-step explanation:
−7(x−3)−27=−6
(-7*x -7*-3) - 27 = -6
-7x + 21 - 27 = -6
-7x - 6 = -6
-7x = 6 - 6
-7x = 0
x = 0
check:
-7(0-3) - 27 = -6
-7*-3 -27 = -6
21 - 27 = -6